2017
DOI: 10.21037/cdt.2017.04.06
|View full text |Cite
|
Sign up to set email alerts
|

The EUROASPIRE surveys: lessons learned in cardiovascular disease prevention

Abstract: The Joint European Societies (JES) guidelines on cardiovascular disease (CVD) prevention published in 1994, 1998, 2003, 2007, 2012 and 2016 defined lifestyle and risk factors targets for patients with coronary or other atherosclerotic disease and people at high risk of developing CVD. Guideline implementation in Europe has been evaluated with four cross-sectional EUROASPIRE surveys starting in mid-1990s. The results showed poor lifestyle and risk factor management in patients with CHD and in high CVD risk peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
2
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 28 publications
3
36
2
6
Order By: Relevance
“…The surveys demonstrate that large proportions of patients do not achieve the recommended targets for CVD prevention. 98 In EUROASPIRE IV, examining 6,187 patients with established CAD, 46% had no T2DM, 19% had newly diagnosed T2DM and 35% had previously known T2DM. The combined use of cardio-protective drugs was 53%, 55% and 60% in these groups.…”
Section: Implementation Of Preventive Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The surveys demonstrate that large proportions of patients do not achieve the recommended targets for CVD prevention. 98 In EUROASPIRE IV, examining 6,187 patients with established CAD, 46% had no T2DM, 19% had newly diagnosed T2DM and 35% had previously known T2DM. The combined use of cardio-protective drugs was 53%, 55% and 60% in these groups.…”
Section: Implementation Of Preventive Measuresmentioning
confidence: 99%
“…It has a long asymptomatic period during which serious complications can develop, there are simple validated questionnaires and reliable diagnostic tests and interventions for glucose, blood pressure and lipids are effective. 97,98 However, large-scale population screening programmes, such as those that have been established for colon and breast cancer, have not been proven to be cost effective for T2DM. If screening through outreach strategies other than the primary care centres were shown to be cost effective and the impressive effects of SGLT2 inhibitors and GLP-1 receptor analogues on cardiovascular outcomes in people with T2DM at high cardiovascular risk also apply to those at lower cardiovascular risk, screening for dysglycaemia in a broader perspective could perhaps be justified.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Especially low control rates were found for LDL-C (4.5%) and body weight parameters (15%). Numerous observational studies, including previous EUROASPIRE surveys, concluded that control of multiple cardiovascular risk factors is poor in clinical practice [20,[23][24][25][26][27], and it is even more difficult to achieve the targets in the primary prevention setting than in coronary patients [20]. In the primary care arm of EUROASPIRE IV, less than half (43%) of the treated patients reached the blood pressure target, one-third (33%) of patients achieved the LDL-C target of <2.5 mmol/L and less than two-thirds (59%) achieved the HbA1c target of <7.0%.…”
Section: Discussionmentioning
confidence: 99%
“…In the primary care arm of EUROASPIRE IV, less than half (43%) of the treated patients reached the blood pressure target, one-third (33%) of patients achieved the LDL-C target of <2.5 mmol/L and less than two-thirds (59%) achieved the HbA1c target of <7.0%. No major differences in the control of lifestyle and risk factors in people at high risk of developing CVD were observed between the EUROASPIRE III and IV surveys [20]. The European Study on Cardiovascular Risk Prevention and Management in Usual Daily Practice (EURIKA) reported that among outpatients with varying degrees of CVD risk, less than half of the treated hypertensive and dyslipidemic patients and a third of the diabetic patients attained treatment goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation